2011
DOI: 10.1103/physrevb.84.054430
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and diffusive nature of LiFePO4investigated by muon spin rotation and relaxation

Abstract: In order to elucidate the magnetism and Li diffusion in LiFePO 4 , we have measured muon-spin rotation and relaxation (μ + SR) spectra for the polycrystalline LiFePO 4 sample in the temperature range between 1.8 and 500 K. Below T N ∼ 52 K, two oscillatory signals together with one fast relaxation signal were clearly found in the zero-field (ZF) μ + SR spectrum. The three signals are reasonably explained using an antiferromagnetic (AF) spin structure proposed by neutron measurements, because electrostatic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
67
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 41 publications
9
67
1
Order By: Relevance
“…6,7 As a result, D Li estimated by 7 Li-NMR for LiCoO 2 and LiNiO 2 8 is three or four orders of magnitude smaller than the D Li predicted by first principles calculations, 9 while μ + SR yields higher D Li for the related compounds LiNiO 2 and LiCrO 2 , more in line with the theoretical predictions. 10 Very recent μ + SR work on the olivine-type lithium iron phosphate LiFePO 4 , which is heavily investigated as a positive electrode material for the near-future Li-ion battery, 11,12 showed that D Li ∼ 3.6 × 10 −10 cm 2 /s at 300 K, 13 a result confirmed by another group. 14 Regarding the reliability of the estimation, the D Li value obtained by μ + SR is consistent with recent electrochemical simulations using the chronoamperometric response data, in which D Li ∼ 7.6 × 10 −11 cm 2 /s for Li 0.999 FePO 4 at ambient temperature (T ), 15 while first-principles calculations predicted D Li ∼ 10 −8 cm 2 /s for the Li 7/8 FePO 4 case.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…6,7 As a result, D Li estimated by 7 Li-NMR for LiCoO 2 and LiNiO 2 8 is three or four orders of magnitude smaller than the D Li predicted by first principles calculations, 9 while μ + SR yields higher D Li for the related compounds LiNiO 2 and LiCrO 2 , more in line with the theoretical predictions. 10 Very recent μ + SR work on the olivine-type lithium iron phosphate LiFePO 4 , which is heavily investigated as a positive electrode material for the near-future Li-ion battery, 11,12 showed that D Li ∼ 3.6 × 10 −10 cm 2 /s at 300 K, 13 a result confirmed by another group. 14 Regarding the reliability of the estimation, the D Li value obtained by μ + SR is consistent with recent electrochemical simulations using the chronoamperometric response data, in which D Li ∼ 7.6 × 10 −11 cm 2 /s for Li 0.999 FePO 4 at ambient temperature (T ), 15 while first-principles calculations predicted D Li ∼ 10 −8 cm 2 /s for the Li 7/8 FePO 4 case.…”
Section: Introductionmentioning
confidence: 75%
“…23,24 However, there is, to our knowledge, no systematic electrochemical work on LiMPO 4 from M = Mn to Ni through Fe and Co, although their magnetic nature has been extensively investigated by several techniques, [25][26][27][28][29][30][31][32][33][34][35] including our μ + SR work at low T . 13,36 In particular, all four compounds exhibit a magnetic transition from a Curie-Weiss paramagnetic phase to an antiferromagnetic (AF) ordered phase at T N = 23 to 53 K.…”
Section: Introductionmentioning
confidence: 99%
“…This is a highly unsatisfactory situation, since D Li is one of the primary parameters that govern the charge and discharge rate of a Li-ion battery, particularly in the case of future solid state batteries. We have, therefore, attempted to measure D Li for layered lithium-transition-metal-oxides with µ + SR since 2005 [14][15][16][17][18][19][20]. Muons do not feel fluctuating magnetic moments at high T , but instead sense the change in nuclear dipole field due to Li diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…This method gives a unique direct access to one of the most important material properties, namely the intrinsic Li-ion self-diffusion constant D Li . We have shown from our extensive measurements of Li-ion cathode materials [3][4][5][6][7][8]11] how the knowledge of such vital information will be crucial for the understanding of solid state ionics in these compounds. This is an important first step towards the materials development needed for future solid state batteries (SSB).…”
Section: Summary and Prospectmentioning
confidence: 99%
“…Recently, it was found that µ + SR detects a slight variation of an internal magnetic field (H int ) due to Li diffusion even for materials containing magnetic ions [3][4][5][6][7][8][9][10], since the implanted muons sense H int with a zero applied field (ZF) in contrast to Li-NMR. Furthermore, making comparison between µ + SR and neutron scattering for detecting D Li from a viewpoint of time window, µ + SR is a very good complementary technique to quasi-elastic neutron scattering (QENS) in the research of Li diffusion in solids (see Fig.…”
Section: Introductionmentioning
confidence: 99%